2004
DOI: 10.1111/j.0962-1075.2004.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation in cowpea bruchid guts during adaptation to a plant defence protease inhibitor

Abstract: Cowpea bruchid, when fed on a diet containing the soybean cysteine protease inhibitor soyacystatin N (scN), activates an array of counter-defence genes to adapt to the negative effects of the inhibitor and regain its normal rate of feeding and development. A collection of 1920 cDNAs was obtained by differential subtraction with cDNAs prepared from guts of the 4th instar larvae of scN-adapted (reared on scN-containing diet) and scN-unadapted (reared on regular scN-free diet) cowpea bruchids. Subsequent expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 51 publications
2
57
1
Order By: Relevance
“…Quantitative changes include generalized or specific increases in the levels of gut proteases to attain optimal rate of protein digestion [2,57,77,78]. Qualitative responses include synthesis of "insensitive" protease isoforms which the PI is unable to bind to and inhibit [1,59,[79][80][81][82], or which have the ability to bind and degrade the PI [38,66,68,[83][84][85]. Though the insect has a choice of combining these adaptive responses, adaptation is achieved only if the insect successfully metabolizes the altered diet and continues normal growth and development.…”
Section: Evolution and Adaptation: Lessons From The Past But Can We mentioning
confidence: 99%
“…Quantitative changes include generalized or specific increases in the levels of gut proteases to attain optimal rate of protein digestion [2,57,77,78]. Qualitative responses include synthesis of "insensitive" protease isoforms which the PI is unable to bind to and inhibit [1,59,[79][80][81][82], or which have the ability to bind and degrade the PI [38,66,68,[83][84][85]. Though the insect has a choice of combining these adaptive responses, adaptation is achieved only if the insect successfully metabolizes the altered diet and continues normal growth and development.…”
Section: Evolution and Adaptation: Lessons From The Past But Can We mentioning
confidence: 99%
“…Compared with WT-WCR adults, the RR-WCR survived longer on soybean plant tissues and displayed more herbivory (14), which can prolong their residence time and opportunities to lay eggs in soybean fields. Moreover, the activity of gut cysteine proteases-the main group of enzymes responsible for WCR protein digestion (15, 16)-was also higher in RR-WCR guts, suggesting a physiological adaptation to CystPIs via enhanced proteolysis, similar to examples in other herbivorous species (14,17,18). However, because the expression of WCR protease genes in the two phenotypes could not fully explain differences in enzyme activity, contributions from microbial factors have been suggested (14).…”
mentioning
confidence: 99%
“…Unlike other proteases of the papain family, cathepsin B and cathepsin B-like homologues bear an extra structural element, the 'occluding loop', that physically hinders the substrate binding cleft and prevents free access to the inhibitory loops of large competitive inhibitors such as cystatins (Musil et al, 1991;Illy et al, 1997). In agreement with these structural inferences, a bacterially expressed variant of CmCatB1, a midgut cathepsin B-like enzyme synthesized de novo in the cowpea weevil C. maculatus challenged with dietary cystatins (Liu et al, 2004;Moon et al, 2004), was shown recently to bear an occluding loop-like structure, slightly Plant cystatins against the banana weevil Page 17…”
Section: Discussionmentioning
confidence: 89%